Cultural, economic, and settlement shifts over the last 9,000 years at Kakapel Rockshelter, Western Kenya - Steven T. Goldstein; Natalie G. Mueller; Emma Finestone; Elizabeth A. Sawchuk; Sara Juengst; Anthony Odera Otwani; Jennifer M. Miller; Michelle C. Langley; Ricardo Fernandes; Axel Steinhof; Victor Iminjili; Christine Chepkorir; et al. (PLoS ONE, 2025)
The spread of food production in sub-Saharan Africa involved multi-directional dispersals of domesticated plant and animal species, often associated with major migrations. The Lake Victoria Basin of eastern Africa was likely an important crossroads in this process, hosting interactions between diverse populations with hunter-gatherer, mobile pastoralist, and farming lifeways in the Holocene. Recent discovery of a large assemblage of ancient domesticated plant remains at Kakapel Rockshelter in the Chelelemuk Hills of Busia County, western Kenya have provided new insights into the timing for when different domesticated crops were adopted within this key region. Here, we expand on the archaeological and cultural context for these findings by reporting results of field excavations, regional surveys, radiocarbon dating, and artifact analyses for deposits recovered from Kakapel Rockshelter dating over the last 9,000 years. Multiple occupational episodes with distinct cultural and technological traits are apparent including Early Holocene foragers, Early Iron Age agropastoralists, and multiple Later Iron Age populations. Agropastoralism first appears here by c. 2400 BP, but it is not until the introduction of sorghum and finger millet after c. 1200 BP in association with arrivals of new groups with Nilotic ancestry that we document the shift to a higher density of sites and longer-term settlement in the region.